2021
DOI: 10.11648/j.ss.20211002.14
|View full text |Cite
|
Sign up to set email alerts
|

Gender System Justification, Gender Differences and Attitudes Towards Women’ Victimization

Abstract: According to the literature, women are actively participating in the victimization of their group because of their positive attitude towards established societal norms. This thesis is supported within the theoretical framework of system justification, which defends the thesis that individuals, both men and women, are motivated to perceive existing social arrangements as fair and legitimate. In this sense, it is admitted that women who strongly justify the gender system are less motivated to adopt collective be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…Unlike other studies which reported a positive relationship between domestic violence and the legitimization of relations of domination between men and women [14,43,46], the results of the present work reveal that experienced domestic violence is negatively related to gender system justification. This observation could be explained by the fact that through its capacity to involve an awareness of one"s own experience of domestic violence, the experienced domestic violence could encourage the questioning of hegemonic and dominant discourses which promote adherence to stereotypes denying and at the same time justifying domestic violence [9,45].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Unlike other studies which reported a positive relationship between domestic violence and the legitimization of relations of domination between men and women [14,43,46], the results of the present work reveal that experienced domestic violence is negatively related to gender system justification. This observation could be explained by the fact that through its capacity to involve an awareness of one"s own experience of domestic violence, the experienced domestic violence could encourage the questioning of hegemonic and dominant discourses which promote adherence to stereotypes denying and at the same time justifying domestic violence [9,45].…”
Section: Discussioncontrasting
confidence: 99%
“…As a result, within the Bamilé ké and Bé ti ethnic groups, for example, women can be victims of domestic violence if they are not submissive to their husbands, considered the head of the household [32]. Among the Bé ti specifically, women come to sing a hymn legitimizing domestic violence which is declaimed in these terms: "I like it when my husband beats me, there I feel that my lion still has all his strength" [14,34].…”
Section: Experienced Domestic Violence: a Traumatic Situationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is undoubtedly with a view to overcoming this linguistic limit that it has been suggested to researchers interested in the evaluation of Stockholm syndrome to take into account cultural differences (notably language) when administering this instrument [51]. In this perspective, the present research, which wants to fill this methodological limit linked to language, sets itself the objectives of: 1) translating and validating the French version of the scale for identifying reactions to Stockholm syndrome among Cameroonian women living in couples and victims of domestic violence; and 2) link the phenomenon of Stockholm syndrome to gender-related attitudes and ideologies, particularly because Stockholm syndrome can be linked to issues relating to the unequal distribution of power between partners; a predominant characteristic of patriarchal societies like those in which Cameroonian women live [22][23][24].…”
Section: Introductionmentioning
confidence: 99%